KETELADANAN GIDEON BERDASARKAN HAKIM-HAKIM 6:12 DIAPLIKASIKAN TERHADAP MAHASISWA DALAM BERKOMUNIKASI DI DEPAN UMUM - Andina Dungu Ataria; Michael Christianto, M. Th (FILADELFIA: Jurnal Teologi dan Pendidikan Kristen, 2021)
How Gideon's example as a valiant hero can be seen in the book of Judges, and also how the humble Gideon was changed and used by God to be a leader for the Israelites. This example is a behavior that can be imitated for others, through attitudes, behavior, morals and also through actions. Gid eon was a humble man, when he met God he experienced a change from being afraid to being brave in doing God's will to restore the Israelites from the oppression of the Midianites.Communication in public is to convey information in front of many people. Barriers in communicating in public when experiencing lack of confidence are nervous, afraid, not mastering the material, so that when conveying information in public they become afraid and feel inferior. The purpose of this study is to find out Gideon's example as a valiant hero. The method used is a qualitative and quantitative methodology. Qualitative (Combined) because by using various sources and conducting research directly. God uses people not from an educational background, but God sees the potential of each person. When communicating in public to be able to be a blessing to others and bring about a change